Cystic fibrosis in Europe: improved lung function and longevity – reasons for cautious optimism, but challenges remain - Kerem, Eitan; Orenti, Annalisa; Adamoli, Arianna; Hatziagorou, Elpis; Naehrlich, Lutz; Sermet-Gaudelus, Isabelle (The European respiratory journal, 2024)
Prognosis and disease severity in cystic fibrosis (CF) are linked to declining lung function. To characterise lung function by the number of adults in countries with different levels of Gross National Income (GNI), data from the European Cystic Fibrosis Society Patient Registry were utilised. Annual data including age, forced expiratory volume in 1 s (FEV ), anthropometry, genotype, respiratory cultures and CF-related diabetes (CFRD) were retrieved between 2011 and 2021. All countries were stratified into GNI per capita to reflect differences within Europe. A consistent improvement in FEV % pred and survival was observed among the 47 621 people with CF (pwCF), including subjects with chronic infection, CFRD and/or undernutrition. Mean values of FEV % pred changed from 85% to 94.2% for children and from 63.6% to 74.7% for adults. FEV % pred further increased among those carrying the F508del mutation in 2021, when elexacaftor/tezacaftor/ivacaftor was available. The number of adult pwCF increased from 13 312 in 2011 to 21 168 in 2021, showing a 60% increase. PwCF living in European lower income countries did not demonstrate a significant annual increase in FEV % pred or in the number of adults. This pan-European analysis demonstrates a consistent improvement in FEV % pred, number of adult pwCF and survival over the last decade only in European higher and middle income countries. Urgent action is needed in the lower income countries where such improvement was not observed. The notable improvement observed in pwCF carrying the F508del mutation emphasises the need to develop treatments for all CF mutations.